(untitled) (KASBIT Business Journal, 2021)
The modern complex business environment requires managers to be equipped with appropriate knowledge, skill-sets, and tools to perform effectively and efficiently. In that context the role of business schools cannot be overemphasized. Accordingly, the faculty members of business schools are expected to possess requisite competencies and skills for performing their responsibilities properly. To achieve this purpose, a systematic process of TNA, that is, Training Need Analysis should arguably exist. This study focuses on examining the impact of training needs analysis on the performance of faculty members in business schools at Karachi. This study employs positivism philosophy, and a deductive approach. Survey strategy was used to plan the various tasks associated with this study. A questionnaire was sent to faculty members of business schools operating in Karachi. Four bi-variate regressions were run, each representing independent variable being regressed by one of the four independent variables. The results showed that, as indicated by the high betas from the regressions, training needs analysis has a strong impact on the performance of faculty members at business schools in Karachi.